Association of Inflammation-Related Gene Polymorphisms With Susceptibility and Radiotherapy Sensitivity in Head and Neck Squamous Cell Carcinoma Patients in Northeast China - Li, Ying; Zhu, Li; Yao, Hongmin; Zhang, Ye; Kong, Xiangyu; Chen, Liping; Song, Yingqiu; Mu, Anna; Li, Xia (Frontiers in Oncology, 2021)
Background: Inflammation-related gene polymorphisms are some of the most important determinants for cancer susceptibility, clinical phenotype diversity, and the response to radiotherapy and chemotherapy. However, the relationship between these polymorphisms and head and neck squamous cell carcinoma (HNSCC) remains unclear. The aim of this study was to investigate the role of inflammation-related gene polymorphisms in the developmental risk and radiotherapy sensitivity of HNSCC. Methods: The Matrix-Assisted Laser Desorption Ionization Time of Flight (MALDI-TOF) genotyping system was used to genotype 612 individuals from a Chinese population for 28 inflammation-related gene polymorphisms. Results: The protein kinase B (AKT1) rs1130233 TT, dominance model (CT+TT vs. CC), recessive model (TT vs. CT+CC), and rs2494732 CC genotypes were associated with reduced risk of HNSCC (P=0.014; P=0.041; P=0.043). The polymeric immunoglobulin receptor (PIGR) rs291097 GA, dominance model (GA+AA vs. GG), and rs291102 dominance model (GA+AA vs. GG) were associated with increased risk of HNSCC (P=0.025; P=0.025; P=0.040). The interleukin-4 receptor-α (IL-4RA) rs1801275 AA genotype was significantly correlated with increased radiotherapy sensitivity of HNSCC patients (P=0.030). In addition, age ≤ 60 years, non-smoker status, and normal levels of squamous cell carcinoma antigen (SCC) were found to be associated with increased radiotherapy sensitivity of HNSCC patients (P=0.033; P=0.033; P=0.030). Conclusion: The AKT1 rs1130233, AKT1 rs2494732, PIGR rs291097, and PIGR rs291102 polymorphisms were significantly related to the risk of HNSCC. The IL-4RA rs1801275 polymorphism, age ≤ 60 years, non-smoker status, and normal levels of SCC were significantly associated with increased radiotherapy sensitivity of HNSCC.